Developing the Muhasabah–Tabayyun–Ishlah (MTI) Model: Integrating Qur'anic Values into Educational Supervision - Rizkan Abqa; Khairiani (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
Islamic educational supervision management continues to be dominated by administrative and mechanistic approaches, while the integration of Qur'anic values into academic supervision practices remains underdeveloped. This study aims to analyze the implementation of the Qur'anic principles of muhasabah, tabayyun, and ishlah in academic supervision and to develop the Muhasabah–Tabayyun–Ishlah (MTI) Model at MIS Al Washliyah Aceh Tengah. The study employed a qualitative approach using an intrinsic case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving the madrasah principal, supervisors from the Ministry of Religious Affairs, and teachers. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by source and methodological triangulation. The findings reveal that educational supervision has evolved from a bureaucratic control mechanism into a process of professional development grounded in Qur'anic values. Muhasabah fosters self-reflection and moral accountability prior to evaluation, tabayyun ensures objectivity through evidence verification and collaborative dialogue, while ishlah translates supervisory findings into professional mentoring and continuous improvement. The integration of these three principles cultivates a supervisory culture that is reflective, dialogical, participatory, and oriented toward continuous improvement in instructional quality. The principal contribution of this study is the formulation of the Muhasabah–Tabayyun–Ishlah (MTI) Model, an operational framework for academic supervision that integrates Qur'anic values with contemporary supervision practices. This model enriches the field of Islamic educational management by offering a supervision approach that combines spiritual accountability, professional objectivity, and continuous improvement within a coherent supervisory framework.